A New Approach for Dimensional Optimization of Inverters in 6T-Static Random-Access Memory Cell Based on Silicon Nanowire Transistor - Hashim, Yasir (American Scientific Publishers, 2017)
This study explores dimensional optimization at different high logic-level voltages for six silicon nanowire transistor (SiNWT)-based static random-access memory (SRAM) cell. This study is the first to demonstrate diameter and length of nanowires with different logic voltage level (Vdd) optimizations of nanoscale SiNWT-based SRAM cell. Noise margins and inflection voltage of butterfly characteristics are used as limiting factors in this optimization. Results indicate that optimization depends on nanowire dimensions and Vdd. The increase in Vdd from 1 V to 3 V tends to decrease the dimensions of the optimized nanowires but increases the current and power. SRAM using nanowire transistors must use Vdd of 2 or 2.5 V to produce SRAM with lower dimensions, inflection currents, and power consumption.